Efektivitas Massage Effriction Terhadap Penurunan Nyeri pada Pasien Cedera Bahu - Fariz Putra Rahmadhan; Dindin Abidin; Aji Margetri Alhafizh (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to determine the effectiveness of effriction massage in reducing chronic shoulder pain in patients at the MPCO Kitau Clinic, Bekasi City. This method uses a Pre-experimental design with One Group Pretest-Posttest Design. The population in this study were patients with chronic shoulder injuries who came to the MPCO Kitau Independent Practice, Bekasi City. The sampling technique used purposive sampling in accordance with the inclusion criteria of 30 samples. The instrument used to measure the pain scale was the Visual Analogue Scale (VAS). The data analysis technique used quantitative descriptive, hypothesis testing used the Paired Sample t-test with a significance level of 0.05. The results showed that the average pain level before treatment (pretest) was 6.53, then decreased after treatment (posttest) to 4.80, with a difference of 1.733. The results of the statistical test showed a p-value of 0.000 (p <0.05), which indicates a significant difference between pain levels before and after the intervention. Based on these results, it can be concluded that effriction massage is effective in reducing chronic shoulder pain and can be used as a non-pharmacological therapy in rehabilitation programs for patients with chronic shoulder pain. Keywords: Shoulder Injury, Effriction massage, Pain